Maulana Syaikh TGKH. Muhammad Zainuddin Abdul Madjid's Educational Leadership Model in Relevance to the Implementation of the Independent Learning Curriculum - Firman Aulia , M. Ayatullah (Mudir : Jurnal Manajemen Pendidikan, 2023)
Maulana Syaikh TGKH. Muhammad Zainuddin Abdul Madjid, in the world of education and his leadership, is one of the figures who changed the face of Indonesian Islamic education for the better. This success certainly cannot be separated from the leadership model that made the Prophet, his teachers, and the Imams of the Ahlu Sunnah Wal Jama'ah as sources of blessings, advice, and role models for becoming leaders. He instilled educational leadership in his thoughts and actions and then tried to pass this on to his students through the Nahdlatul Wathan organization, Nahdlatul Wathan madrasas; from there, they became cadres by strengthening their faith and Ta'wa through social, educational, and da'wa channels. Wow, so with the development of educational facilities throughout the archipelago to eradicate religious and ethical blindness, the result is that his educational leadership is a leadership paradigm that is related to the leadership concept of the Apostles and is detailed in the concepts of the friends of the Prophet Muhammad. This research uses a literature review method to discuss the idea of an educational leadership model in terms of humanizing, liberating, and transcending the Islamic educational leadership model, as well as the relevance of implementing the independent learning curriculum.